Geochemical characteristics of gases associated with natural gas hydrate - Li, Yuanyuan; Chang, Jingyi; Lu, Hailong (Frontiers in Marine Science, 2022)
With more natural gas hydrate samples recovered and more research approaches applied to hydrate-associated gas studies, data concerning the geochemical characteristics of hydrate-associated gases have been increased significantly in the past decades. Although systematic reviews of hydrocarbons are available, fewer studies have focused on the systematic classification of gas hydrates, yet. In this study, the primary origins and secondary processes that affect the geochemical characteristics of the gases are discussed. The primary origins are affected mainly by the type and /or maturity of the organic matter, which determine the main signature of the gas is microbial gas or thermogenic gas in a broad scheme. Apart from primary origins, secondary processes after gas generation such as migration, mixing, biodegradation and oxidation occur during the migration and/or storage of gases can significantly alter their primary features. Traditional methods such as stable isotope and molecular ratios are basic proxies, which have been widely adopted to identify these primary origins and secondary processes. Isotopic compositions of C2+ gases have been employed to identify the precursor of the gases or source rocks in recent years. Data from novel techniques such as methane clumped isotope and noble gases bring additional insights into the gas origins and sources by providing information about the formation temperature of methane or proxies of mantle contribution. A combination of these multiple geochemical approaches can help to elucidate an accurate delineation of the generation and accumulation processes of gases in a gas hydrate reservoir.